Analisis Penalaran Matematis Ditinjau Dari Kemampuan Awal Matematika Siswa Kelas VIII SMPN 22 Mataram - Hana Rippana De Yumaina; Nani Kurniati; Eka Kurniawan (Mandalika Mathematics and Educations Journal, 2026)
The purpose of this study is to describe the mathematical reasoning abilities of eighth-grade students at SMPN 22 Mataram in the 2025/2026 academic year based on their initial mathematical ability levels. This is a descriptive study using a qualitative approach. The data collection techniques used in this study include administering a written test of initial ability, a written test of mathematical reasoning ability, and in-depth interviews regarding students’ mathematical reasoning ability. The data analysis methods employed are data reduction, data presentation, and conclusion. The indicators of mathematical reasoning ability consist of four stages, namely: a) identifying information, b) mathematical manipulation, c) constructing evidence, providing reasons or evidence for the validity of a solution, and d) concluding statements. The research results indicate that: a) students with high initial ability were able to solve the mathematical reasoning ability test questions well and met all 4 indicators of mathematical reasoning ability, b) students with moderate initial ability were less able to solve the mathematical reasoning ability test questions well, and errors and mistakes were found across the 4 stages of the mathematical reasoning ability indicators, c) students with low initial mathematical ability were able to solve the mathematical reasoning ability test questions up to the stage of formulating evidence, providing reasons or evidence for the correctness of the solution, but there were many errors and mistakes.